Legislación de emergencia y reforma laboral en España (2011-2012) - Sempere, Antonio (Pontificia Universidad Católica del Perú. Fondo Editorial, 2012)
Emergency legislation and labor reform in Spain(2011-2012)Spanish Labor Law is going through a phase of continuous and disordered reforms, most of them made through approved rules by the Government invoking raisons of urgency. Here are explained six recent andrelevant Royal Decrees-Laws approved between 2010 and 2012

El Derecho del Trabajo español está atravesando una etapa de continuas y desordenadas reformas, la mayoría de ellas realizadas a través de normas aprobadas por el Gobierno invocando razones de urgencia. Aquí se da cuenta de seis reales decretos leyes recientes y relevantes aprobados entre2010 y 2012.
Keywords: Reforma laboral; Legislación laboral de emergencia; https://purl.org/pe-repo/ocde/ford#5.05.00